Enumeration of WT1‐specific CD8+ T cells for clinical application using an MHC Streptamer based no‐wash single‐platform flow‐cytometric assay. Issue 10 (25th May 2017) - Matko, Sarah; Teichert, Madeleine; Tunger, Antje; Schmitz, Marc; Bornhauser, Martin; Tonn, Torsten; Odendahl, Marcus
Abstract: The advent of novel strategies to generate leukemia‐associated‐antigen (LAA)‐specific T cells for adoptive immunotherapies creates a demand for standardized good laboratory practice (GLP)‐compliant enumeration assays to provide a secure clinical environment—whether it is to identify potential donors, define therapeutic doses for transplantation, or monitor clinical success. Here, we introduce a no‐wash assay based on single‐platform cell enumeration and Streptamer staining to determine the Wilms' tumor antigen 1 (WT1)‐specific T cell immunity in clinical samples. We analyzed the performance of the WT1‐specific MHC Streptamers in direct comparison to CMV‐ and EBV‐specific MHC Streptamer staining by spiking antigen‐specific T cells in PBMCs. The accuracy of the assay was high for all performed experiments with a mean recovery of 94% and a linear regression of 0.988. Differences were apparent regarding the limit of detection/quantification (LOD/LOQ). While results obtained for WT1 yielded an LOD/LOQ of 0.08 ± 0.04% and 0.11 ± 0.06% (1.33 ± 0.32 cells/µl and 1.9 ± 0.14 cells/µl), the overall LOD/LOQ was notably lower and accounted to 0.02 ± 0.02% and 0.05 ± 0.03% (0.60 ± 0.03 cells/µl and 1.27 ± 0.58 cells/µl). Subsequent screening of 22 healthy individuals revealed significantly higher values for WT1 (0.04 ± 0.02% and 1.5 ± 0.9 cells/µl) than for the irrelevant HIV pol (0.016 ± 0.01% and 0.5 ± 0.4 cells/µl). In contrast, no increased frequencies were observed for WT1‐specific T cells compared to HIV‐specific T cells using a classical wash‐protocol. These findings strongly suggest the use of no‐wash single‐platform assays in combination with MHC Streptamer staining for the detection of low affinity LAA‐specific T cells due to its high accuracy and sensitivity. © 2017 International Society for Advancement of Cytometry